VEXAS Syndrome and Alzheimer’s Disease—Are There Connections? - Aleksandra Sowa; Marta Malicka; Magdalena Biernacka; Jan Aleksander Beszłej; Jerzy Leszek (Brain Sciences)
VEXAS syndrome and Alzheimer’s disease (AD), though distinct in clinical manifestations, share overlapping pathophysiological mechanisms, including systemic inflammation, protein misfolding, and vascular dysfunction. VEXAS syndrome, a rare autoinflammatory disorder characterized by somatic UBA1 mutations, systemic inflammation, and hematologic abnormalities, presents primarily in older males. Meanwhile, AD, the leading cause of dementia, involves progressive neurodegeneration driven by amyloid-beta plaques, tau tangles, and chronic neuroinflammation. This article explores potential connections between the two conditions, focusing on inflammation, neurovascular changes and cellular stress. Systemic inflammation observed in VEXAS syndrome may potentiate neuroinflammatory processes in Alzheimer’s disease (AD), as circulating proinflammatory cytokines have the capacity to cross the blood–brain barrier (BBB), thereby inducing glial activation and promoting neuroinflammation. Additionally, coexisting vascular dysfunctions characteristic of both conditions may synergistically contribute to accelerated cognitive decline. Both conditions involve disruption of the ubiquitin–proteasome system, with UBA1 mutations being specific to VEXAS. Given the established role of UBA1 in maintaining neuronal homeostasis, investigating the overlapping and distinct molecular mechanisms may provide valuable insights into their pathophysiology. The review underscores the need for further research to elucidate these links and improve therapeutic strategies, especially for individuals affected by both disorders.